The politics of crime control: essays in honour of David Downes - Newburn, Tim; Downes, David (Clarendon studies in criminology, 2006)
David Downes: an introduction / Tim Newburn and Paul Rock -- Beyond risk: a lament for social democratic criminology / Robert Reiner -- Dangerous people: beginnings of a New Labour proposal / Andrew Rutherford -- With respect to order, the rules of the game have changed: New Labour's dominance of the 'law and order' agenda / Rod Morgan -- East Ending: dissociation, de-industrialization and David Downes / Dick Hobbs -- Opportunity makes the thief-taker: the influence of economic analysis on crime control / Lucia Zedner -- Contrasts and concepts: considering the development of comparative criminology / Frances Heidensohn -- Historicizing contrasts in tolerance / Nicola Lacey -- Contrasts in intolerance: cultures of control in the United States and Britain / Tim Newburn -- Governance and restorative justice in Cali, Colombia / Declan Roche -- Neither honesty nor hypocrisy: the legal reconstruction of torture / Stanly Cohen